2015
DOI: 10.1021/acs.iecr.5b03608
|View full text |Cite
|
Sign up to set email alerts
|

Esterification Kinetics of Tributyl Citrate Production Using Homogeneous and Heterogeneous Catalysts

Abstract: In this work, the production of tributyl citrate via catalytic and self-catalyzed esterification of citric acid with 1-butanol was studied. Both, methanesulfonic acid (MSA) and Amberlyst 70 ion-exchange resin were evaluated as catalysts in the reaction. The kinetic effects of the temperature (353–393 K), the feed molar ratio of alcohol to acid (8:1 to 16:1), and catalyst loadings (0.5–1.5 wt % of MSA, and the equivalent amount of Amberlyst 70) were evaluated. Experiments were carried out using stirred batch re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…However, homogenous catalysts are generally known for being very corrosive, formation of high byproduct, difficult to reuse along with pollution issues. In contrast, using heterogeneous catalysts as good alternative, which offer high catalytic efficiency, and less corrosive activity as ion exchange resins 57 . Wang et al 60 developed an eco‐friendly heterogenous catalyst which is easy to separate with high catalytic activity for the synthesis of TBC.…”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
See 1 more Smart Citation
“…However, homogenous catalysts are generally known for being very corrosive, formation of high byproduct, difficult to reuse along with pollution issues. In contrast, using heterogeneous catalysts as good alternative, which offer high catalytic efficiency, and less corrosive activity as ion exchange resins 57 . Wang et al 60 developed an eco‐friendly heterogenous catalyst which is easy to separate with high catalytic activity for the synthesis of TBC.…”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…Despite the merits of heterogenous catalyst, when comparing between using homogenous and heterogenous catalysts to produce TBC and TEC, it does not always guarantee the highest yield. Kinetic studies found that at specified conditions the homogenous catalyst (methane sulfonic acid), showed a higher catalytic performance compared to the heterogenous one (Amberlyst 70) for TBC 57 and for TE 61 …”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…The response factor was assumed to have linear proportionality with respect to the molecular weight of the citrate species, as successfully implemented in a previous work. 5 The developed technique allowed measuring citrate species only; therefore, the n-butanol concentration was obtained by difference. Acid−base titration was used to verify the purity of DBC during the extraction process.…”
Section: Methodsmentioning
confidence: 99%
“…TBC synthesis proceeds through direct esterification of citric acid with n -butanol, involving a set of series-parallel equilibrium reactions (Figure ). As the citric acid contains three carboxylic groups, each intermediate ester, monobutyl citrate (MBC) and dibutyl citrate (DBC), can have two different structural isomers. In the case of MBC, the butyl-branched substituent can be located in a carboxyl group adjacent to a secondary carbon (2-hydroxy-1,2,3-propanetricarboxylic acid-1-butyl ester; MBC Isomer 1) or to a quaternary carbon (2-hydroxy-1,2,3-propanetricarboxylic acid-2-butyl ester; MBC Isomer 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation